Hearing care and management priority among parents of children with Down syndrome: a grounded theory. (2nd August 2021) - Whicker, John J.; Muñoz, Karen; Pearson, Nicole J.; Landon, Trenton J.; Nelson, Lauri H.; White, Karl R.; Twohig, Michael P.
Abstract: Objective: This study qualitatively explored the factors that influence how parents of children who are Deaf or hard-of-hearing with Down syndrome prioritise hearing care and management and developed an associated theory to explain that priority. Design: Grounded theory was used for the purposes of this qualitative study. Data were collected using in-depth interviews which were analysed using a three-tiered qualitative coding process. Study Sample: Eighteen mothers of children who are Deaf or hard-of-hearing with Down syndrome participated in this study. Results: The higher the extent of engaged professional support, perception of benefit for child, parent activation, and family engagement, the higher the priority for hearing care and management will likely be among parents of children who are Deaf or hard-of-hearing with Down syndrome. Conclusions: Understanding how parents of children who are Deaf or hard-of-hearing with Down syndrome decide to prioritise hearing care and management has implications for how hearing health providers and others provide care to parents to enhance priority for hearing-related needs.